Lossless and Near-Lossless Audio Compression Using Integer-Reversible Modulated Lapped Transforms - Malvar, Henrique S. (Data Compresison Conference, 2007)
We present a simple lossless audio codec, composed of an integer-reversible modulated lapped transform (MLT) followed by a backward-adaptive run-length/Golomb-Rice (RLGR) encoder. Its compression performance matches those of state-of-the-art predictive codecs, and it has the advantage that its compressed bitstream contains frequency-domain data that can be used for applications such as search, identification, and visualization. Its compression gain can be improved through a novel data model based on cross-block smoothed spectral magnitude estimates. Its bitstream can be transcoded into a lossy format, for transfers to portable players, at about twice the speed of other codecs. The codec also supports a near-lossless mode, which allows for an extra factor of two in compression without noticeable distortions.